Contorted heteroannulated tetraareno(a,d,j,m)coronenes - Yang, Xuan; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2021)
Fused polycyclic aromatic compounds are interesting materials for organic electronics applications. To fine-tune photophysical or electrochemical properties, either various substituents can be attached or heteroatoms (such as N or S) can be incorporated into the fused aromatic backbone. Coronenes and heterocoronenes are promising compounds in this respect. Up until now, the possibilities for varying the attached fused heteroaromatics at the coronene core were quite limited, and realizing both electron-withdrawing and -donating rings at the same time was very difficult. Here, a series of pyridine, anisole and thiophene annulated tetraareno[a,d,j,m]coronenes has been synthesized by a facile two-step route that is a combination of Suzuki-Miyaura cross-coupling and a following cyclization step, starting from three different diarenoperylene dibromides. The contorted molecular π-planes of the obtained cata-condensed tetraarenocoronenes were analyzed by single-crystal X-ray crystallography, and the photophysical and electrochemical properties were systematically investigated by UV/Vis spectroscopy and cyclovoltammetry.